The attitude and commitment of the Malaysian government towards Islam in the foreign policy (1957-2003): An assessment - Robani, Anidah (Institute of Tun Dr. Mahathir Mohamad’s Thoughts, Universiti Utara Malaysia, 2010)
Malaysia can be classified as a Muslim country. With its Muslim majority and Islam as its official religion, Malaysia takes considerable pride for being part of the dynamic and progressive Islamic Ummah. Being part of the Ummah, Malaysia endeavors her utmost to manifest her concern and commitment to the Islamic principles of brotherhood and justice. Islam plays an important part in the national life, as it is closely linked to the ethnic identity of the politically dominant Malays. Consequently, the foreign policy of Malaysia may be said to be affected by Islam to a considerable degree. The primary concern of this paper is to examine Malaysia’s commitment to Islam and Islamic cause, as refl ected in its foreign policy. It is also, in a way, an attempt to identify the prime mover of Malaysian foreign policy. This paper, argues that Islam has never been an overriding factor in Malaysia’s support for Islamic issues. Malaysian’s role in this respect was largely motivated by pragmatic considerations resulting from an interplay between various factors; political, economic, religious and humanitarian.